Peningkatan Kapasitas Petani Melalui Pelatihan Pemupukan Tanaman Padi di Provinsi Sumatera Utara - Miyarnis, Miyarnis; Dewi, Dora Silvia; Budiwan, Diah Wiyani (UNIVERSITAS LABUHANBATU, 2024)
To increase farmers knowledge and skills in managing rice fertilization, the government and related institutions have implemented various fertilizer training programs. This research aims to evaluate the effectiveness of rice fertilizer training in increasing the capacity of farmers in North Sumatra Province. This research was carried out at UPT. Agricultural Training and Mechanization for the Food Security, Food Crops, and Horticulture Service of North Sumatra Province on February 20–23, 2024. This research was carried out on 30 training participants from 12 districts in North Sumatra. The data collected consists of primary data consisting of respondent characteristics and pre-test and post-test results. The data were analyzed with the Minitab applications of tware using non-parametric statistical analysis, namely the Wilcoxon Match Pairs Test with a significance level of 0.05. The increase in knowledge of farmers who took part in rice fertilization training was 32.2%. In general, attitudes and responses are classified as high, namely the benefits of the material provided are 100%, the ease of the material to be appliedis 100%, the excessprofits obtained in applying the material are 100%, the suitability of the material with farming needsis 100%, liking orinterest in the material provided was 100%, the desire to apply the material provided was 83.3%, and the plan to implement the material provided was 80%. Keywords: training, pretest, posttest, fertilizing rice plants